A Review about Stock & Exchange Board of India, Regulation of Business in the Stock Exchanges: An overview of the Stock Exchange Board of India and the regulation of business in the stock exchanges (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Generally, the financial sector divided in 2 parts, Money market as well as capital market. Securities market place is a crucial, structured capital industry where transaction of capital is facilitated using immediate funding with securities as an investment. Securities market can be split into a main market as well as secondary market.